Implementation of Techniques of Advanced Regulatory Process Control Supported on Matlab and on the Compactlogix Platform (2016)
Abstract. This master final work was developed in three stages, the same three parts in which this document has been sectioned. The central themes of the three parts are: Process Modeling, Regulatory Control and laboratory practices. In the stage of process modeling, four industrial processes were modeled from thermodynamic systems theory. The processes worked are a Heat Exchanger, an Industrial Furnace, a Continuous Stirred Tank Reactor and an Absorption Column. The phenomenological models were analyzed and linearized analytically. The models were subsequently implemented on Simulink and validated through simulations. Similarly, these models were emulated and validated coontrol platform CompactLogix. In the second part of this project, five classic techniques of Advanced Regulatory Control were studied and their principles of operation were analyzed and characterized. Specifically, techniques Feedforward Control, Cascade Control, Ratio Control, Override Control and Split-range Control, were worked. The advantages and fields of application of different techniques are discussed herein. Each of the strategies was applied and validated in a case study through implementation and simulation on Simulink, and by implementation and emulation on the CompactLogix platform. In the final part of the project five laboratory practices were structured. These practices aim to transferring the knowledge developed in this project by carrying out theoretical and practical exercises. This practices would be made by students of the Universidad Nacional and engineers in the area of industrial control, in future courses